2021
DOI: 10.1186/s12872-021-02203-2
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of monocytes and endothelial cells isolated from the human aorta suppresses by miRNA-PEI particles

Abstract: Background Knowledge of stenosis in coronary arteries requires an understanding of the cellular and molecular processes that occur throughout the leukocyte rolling process. In this study, the roles of miR-125a-5p and miR-495-3p were investigated on the adhesion of endothelial cells (ECs) isolated from the human aorta. Methods Human primary endothelial cells were obtained from the aorta of people who had died of brain death. Whole blood was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The activated endothelial cells might overexpress adhesion molecules and enhance leukocyte adhesion following rolling, strong adhesion, crawling, and transmigration processes [7]. Many studies showed that non-coding RNAs target the adhesion molecules and other genes involved in vessel stenosis [20][21][22][23][24]. This study was focused on the effects of miRNA-related genes predicted Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activated endothelial cells might overexpress adhesion molecules and enhance leukocyte adhesion following rolling, strong adhesion, crawling, and transmigration processes [7]. Many studies showed that non-coding RNAs target the adhesion molecules and other genes involved in vessel stenosis [20][21][22][23][24]. This study was focused on the effects of miRNA-related genes predicted Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, macrophages by production of matrix metalloproteinase enzymes (MMPs) degrade the extracellular matrix (ECM), causing plaque remodeling [1-3, 5, 6]. In the other hand, micro-RNAs (miRNA/miR) are small nucleotides that affect the cellular pathways via the regulation of gene expression levels [13,20,21]. Many studies reported that micro-RNAs might retard atherosclerosis process by targeting some genes such as adhesion molecules [20,22].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in the above, the neutrophils, leukocytes, and T cells migrate through activated arterial walls, which is a prerequisite step due to the infection or damage [ 32 ]. The entry of cells into the inflamed locations occurs in several stages including the weak adhesion, rolling, and crawling between endothelial cells and leukocytes [ 8 , 33 ] (Fig. 1 ).…”
Section: Recruiting Blood Cells Into Sub-endothelial Space Increases ...mentioning
confidence: 99%
“…VCAM-1 can regulate the in ammatory response of endothelial cells in the whole body and promote the migration of leukocytes after binding to integrin receptor α4β1 (Yousef et al, 2019).Under physiological condition, the expression levels of ICAM-1 and VCAM-1 are relatively low. Environmental stimuli upregulate the expression of these adhesion molecules (Poursaleh et al, 2021;Shen et al, 2021). ICAM-1 and VCAM-1 also participate in BBB permeability change (Walter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%